Importance of Contract Administration for Timely Construction of Hydropower Projects without Disputes - Kayastha, Gyanendra Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Most of the large hydropower projects in the region have been behind schedule than agreed in the contracts. Such delays besides project cost overrun cause direct economic loss to the countries in the form of interest costs, loss of energy revenues and loss in industrial production due to shortage of power. With delays, the Contractor finds ways for claim for additional time and cost. Such a situation may be the result of poor contract administration & management skills. Therefore, a fair and just administration of the contract is key to the successful performance of the contract on time, with respect to both budget and quality with minimum dispute events. DOI: http://dx.doi.org/10.3126/hn.v14i0.11265 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 14, 2014, January Page: 49-51